General pore features for one-step C2H4 production from a C2 hydrocarbon mixture. Issue 32 (17th March 2022) - Zhang, Tao; Cao, Jian-Wei; Zhang, Shu-Yi; Feng, He; Li, Ye; Wang, Yu; Chen, Juan; Wang, Teng; Chen, Kai-Jie
Abstract : The general pore features for one-step C2 H4 production from C2 gas ternary mixture were established. Abstract : Herein, we propose the required general pore features for one-step C2 H4 production from a C2 hydrocarbon mixture, such as: (i) a non-metallic binding site; (ii) polar pore surface; and (iii) narrow pocket. Four representative MOFs (Ni-BDC-INA, CPM-173, UiO-66, and DMOF-1 ) and two counterexamples (MOF-74-Co and IISERP-MOF2 ) were selected to verify this concept, by conducting single-component gas adsorption measurements, multiple-component breakthrough experiments, and molecular simulations. The established pore features are a stepping-stone for the design and synthesis of new MOFs with improved performance for C2 H4 separation.